Traders : risks, decisions and management in financial markets - Fenton-O'Creevy, Mark (Mark P.) (OUP E-Books., 2005)
The authors examine how traders really behave in financial markets, what they do and how they make decisions. The book is also about how traders are managed - the best and worst examples - and about the institutions they inhabit: firms, markets cultures, and theories of how the world works.